Ressonância do patrimônio cultural de Júlio de Castilhos - RS por meio da dança: uma proposta de arte-educação patrimonial - Padilha, Ariella de Oliveira (2024)
This research is part of the Postgraduate Program in Cultural Heritage at the Federal University of Santa Maria, in the research line of History and Heritage. Based on the relationship between art, in this case dance, and cultural heritage, is it possible to think of and propose a form of heritage arts education? The city of Júlio de Castilhos, in the interior of Rio Grande do Sul, has historical records of a people rich in culture, which is little known by its inhabitants, and consequently, there are no effective practices for the appreciation, preservation, and dissemination of this history and its cultural heritage. This situation led to the formulation of the research problem, which, by questioning the feasibility of heritage arts education, aims to explore educational strategies on how the people of Júlio de Castilhos could develop a sense of belonging to the city’s heritage, promoting possibilities for the dissemination and appreciation of our history. Thus, the focus of this research is on artistic-pedagogical actions in the field of dance, which aimed to encourage the people of Júlio de Castilhos to reflect on their origins and feel connected to the history of the city. Dance can lead individuals to understand the environment, culture, and context, and recognize the connections between the individual’s perspective and the group's culture. Based on the methodological approach of A/r/tography, the research emphasized the living process and the researcher’s immersion in the studied context. It also required literature reviews on cultural heritage, arts education, dance, resonance, and heritage education. The research's object of study, which also became its product, was the dance performance "Ecos: bodies that move Vila Rica." This performance was created through a collective creative process with students from the Staff Arte em Dança dance project at Maria Rainha School, who participated in investigative activities about significant cultural heritage sites related to the city’s history, such as Praça João Alvarenga, Clube Félix da Cunha, Sociedade Cultural e Recreativa José do Patrocínio, and Centro Cultural Álvaro Pinto. After the performance, the reflections from the student-performers and the audience were analyzed, highlighting the impact of the production on the community. The audiovisual recording of the dance performance was shared in the municipal schools of Júlio de Castilhos, inspiring new forms of heritage arts education and continuing to spread the local history. It was understood that this research in cultural heritage remains alive and adaptable to the contexts in which it may still be inserted.